The Effect of Profitability, Liquidity, and Leverage on Divi-dend Policy With Company Size as A Moderating Variable in Mining Sector Companies Listed on the IDX - Sabariah Sabariah; Erlina Erlina; Fahmi Natigor Nasution (Harmoni Economics: International Journal of Economics and Accounting, 2025)
Thisastudyaaims toaanalyze theaeffect ofaprofitability, liquidity, and leverage on dividend policy, as well asato examine ahe role of firm size as a moderatingavariable in mining sector companies listed on the IndonesiaaStock Exchangea (IDX) for the 2020 2024 period. Thearesearch employs a quantitative approach using panel data from 63 mining companies over the observation period (315 observations). The analysis was conducted using panel data regression (Common Effect Model), Moderated Regression Analysisa (MRA), aand Autoregressive Distributed Lag (ARDL) to identifyaboth short term and long-term relationships. Tests include classical assumption tests (normality, multicollinearity, heteroscedasticity, and autocorrelation) as well as partial hypothesis testing (t-test) and simultaneous testing (F-test). The results show that profitability (ROA) has a positive and significant effect on dividend policy, indicating that companies with higher profit performance tend to distribute larger dividends. Liquidity (CR) ahas no significant effect, suggesting that mining companies prioritize cash stability to support operations over dividend distribution. Leverage (DER) ahas a negativeaand significant effect, aconsistentawith the Trade-Off Theory which states that high debt limits dividend payments. Firm size does not moderate the relationship between the three variables and dividend policy, reflecting the capital-intensive and high-risk characteristics of the mining sector.